Enhanced Blended Learning within Teaching and Learning - Rina Fadhilah Ismail, Nur Quratun ‘Aini Binti Haron, Rozainun Haji Abd. Aziz, (Opción, 2019)
Blended learning is one of the teaching and learning approaches that benefit from the boundless opportunities of technology developments. Therefore, this study addresses the issue relating to the practicality of blended learning, its enhancement and formulates better concept teaching and learning process. This study also provides propositions at three levels: the university, faculty and individual to establish an enhanced blended learning approach. The results showed that the use of tutorial in online learning was more effective than face-to-face learning.